Analysis of Concrete Strength Analysis K-250 With Additional Asbestos Waste Powder as a Substitute of Fine Aggregate - Ahmad Ridwan; Yosef Cahyo Setianto Poernomo; Edy Garjito; Romadhon (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2024)
Concrete is an important component in the manufacture of infrastructure, but in its various advantages, concrete also has deficiencies in the elements of its manufacturing materials, concrete which can cause environmental damage. Not only that, another problem was also found, namely the amount of asbestos waste being wasted. In addition to being difficult to decipher in nature, asbestos also has an impact on human health, namely lung cancer. From there, researchers are interested in conducting research and finding solutions. The purpose of this research is to find out the results of testing the compressive strength of K-250 concrete with the use of asbestos powder waste and to review the use of asbestos powder waste as fine aggregate efficiency.This study uses an experimental method with data analysis to find the results of testing the compressive strength of K-250 concrete. The test will be carried out on 12 specimens with asbestos waste variance of 0%, 10%, 20%, and 30% as a substitute for fine aggregate. From the test results obtained data on the compressive strength of concrete at the age of 28 days, namely: 0% = 217.8 Kg/cm3, 10% = 238.1 Kg/cm3, 20% = 188.7 Kg/cm3, and 30% = 100 ,1 Kg/cm3, which concludes that K-250 concrete with a variance of 10% meets the compressive strength.